2006
DOI: 10.1103/physrevb.73.024301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of macroscopic structural fluctuations in bcc solidHe4

Abstract: We report neutron diffraction studies of low density bcc and hcp solid 4 He. In the bcc phase, we observed a continuous dynamical behaviour involving macroscopic structural changes of the solid. The dynamical behaviour takes place in a cell full of solid, and therefore represents a solidsolid transformation. The structural changes are consistent with a gradual rotation of macroscopic grains separated by low angle grain boundaries. We suggest that these changes are triggered by random momentary vibrations of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…As a result, internal stress is generated, large enough to cause the crystal to disorder and transform into a polycrystal. This behavior is consistent with what we observed in neutron scattering experiments [1]. It is important to point out that the crystal can be disordered only after the cell is entirely filled with solid.…”
Section: Solidsupporting
confidence: 91%
See 1 more Smart Citation
“…As a result, internal stress is generated, large enough to cause the crystal to disorder and transform into a polycrystal. This behavior is consistent with what we observed in neutron scattering experiments [1]. It is important to point out that the crystal can be disordered only after the cell is entirely filled with solid.…”
Section: Solidsupporting
confidence: 91%
“…During these experiments we grew large (7-10 cm 3 ) single crystals, which sometimes transformed into polycrystals due to some thermal or mechanical stress. In those cases, we noticed that individual crystallites which are part of a polycrystalline solid can spontaneously change their spatial orientation while embedded in the surrounding solid [1]. These orientation changes seemed to be driven by ambient noise, either vibrational or thermal.…”
Section: Solidmentioning
confidence: 99%
“…Similar behavior was observed in neutron scattering experiments 22,23 , with the c axis of hcp crystals again being close to horizontal. Regarding bcc crystals, we found that these typically grow with the [111] direction close to vertical 22,24,23 . Therefore, experiments on different crystals in the same cell are usually quite reproducible, as most of these crystals would grow with the same crystallographic direction with respect to the cell.…”
Section: Experimental Systemmentioning
confidence: 97%
“…For that, we first needed to grow single crystals of helium inside the experimental cell. Our knowledge of single crystal growth comes mainly from neutron scattering experiments [20,17]. During these experiments elastic scattering was used to characterize the quality and orientation of the crystals grown.…”
Section: Crystal Growthmentioning
confidence: 99%